Implementation of peace-love character development in elementary schools - Sendi Fauzi Giwangsa; Bunyamin Maftuh; Mamat Supriatna; I Ilfiandra (Inovasi Kurikulum, 2023)
The persistence of both physical and verbal violence in schools serves as the driving force for this study. Additionally, the teacher's efforts have not been the best in helping the elementary school pupils cultivate a spirit of harmony and nationalism. This study evaluates efforts to instill a love of peace in primary school kids. Utilizing a qualitative approach, this investigation. Interviews, questionnaires, and observational instructions were the instruments employed. According to the research's findings, activities in the classroom, extracurricular activities, and school culture all contribute to developing a peace-loving character in primary school pupils. Classroom activities include incorporating peace-loving values into studies through teaching and learning activities. Extracurricular activities such as scouting, choirs, and martial arts help build peace-loving character development outside the classroom. The developed school culture comprises example behavior from all school stakeholders, habituation, spontaneous activities, and conditioning. AbstrakPenelitian ini dilatarbelakangi oleh masih banyak ditemukannya kasus kekerasan di sekolah, baik itu kekerasan fisik atau verbal. Selain itu belum optimalnya upaya guru dalam mengembangkan karakter cinta damai dan nasionalisme bagi siswa sekolah dasar. Tujuan dari penelitian ini yaitu menganalisis upaya mengimplemntasikan karakter cinta damai bagi siswa sekolah dasar. Penelitian ini menggunakan metode kualitatif. Instrumen yang digunakan yaitu kuisioner, pedoman observasi dan wawancara. Berdasarkan hasil penelitian menunjukkan bahwa upaya pengembangan karakter cinta damai bagi siswa sekolah dasar dilakukan melalui kegiatan di dalam kelas melalui pembelajaran, kegiatan di luar kelas, serta budaya sekolah. Kegiatan di dalam kelas dilakukan melalui mengintegrasikan nilai-nilai cinta damai dalam mata pelajaran melalui kegiatan belajar mengajar. Pengembangan karakter cinta damai melalui kegiatan diluar kelas dilaksanakan melalui berbagi kegiatan ekstrakulikuler seperti pramuka, paduan suara serta pencak silat. Adapun budaya sekolah yang dilakukan untuk mengembangkan budaya sekolah diantaranya yaitu keteladanan dari seluruh stakeholder sekolah, pembiasaan, kegiatan spontan dan pengkondisian.Kata Kunci: Karakter cinta damai; pendidikan cinta damai; siswa sekolah dasar